Metabolie profile test of dairy cattle in Al-Ishaqi plan: A.M.H. Al- judi, H.K. Abood, M.N. Al –Siagh - Al- judi, A. M.H. (The Iraqi Journal of Veterinary Medicine, 2005)
Metabolic profile test was done on Friesian cows of Al-Ishaqi plan. Bloodsamples were collected from 21 cows in the second lactation stage, 7cows withhigh Milk yield, 7cows with moderate milk yield& 7cows with low milk yield.Estimation of the following were done; hemoglobin, packed cell volume bloodurea nitrogen glucose total protein albumin& globulin, in three periods (1monthafter calving, 4month after calving, 7month after calving). The results revealedthat Hb, total protein& globulin ratios were increased, while the albumin ratiowas decreased in the first period, PCV increased in the third period, albuminratios showed higher levels in high milk yield cows, BUN show higher levels inthe first period, increased levels of BUN in high milk yield cows, low levels ofblood glucose in the second period.Signification correlation coefficient betweentotal protein ratios& Hb, globulin ratios& BUN were obtained, while significantnegative correlation between total protein& albumin was existed. Regressionequations between total protein ratios& all blood traits were calculated.